SELECTING THE BEST BANK USING A COMBINATION OF ENTROPY AND PROMETHEE II METHODS - Cindy Saputri; Raden Sulaiman (Universitas Negeri Surabaya, 2026)
Bank are financial institutions that play an important role in meeting the financial needs of the community, including saving funds, channeling credit, and providing financial services. In choosing a bank, prospective customers need to consider various criteria so that the decision taken is objective. This research aims to provide recommendations for choosing the best bank using the Multi Criteria Decision Making (MCDM) method, namely the Entropy and PROMETHEE II methods. Entropy method is used to get the importance weight of each criterion. While the combined Entropy and PROMETHEE II methods are used to obtain the best alternative from a number of alternatives provided. The criteria used in determining customer priorities in choosing a bank are ease of digital services, tangibles, reliability, responsiveness, assurance, empathy, bank and ATM accessibility. In addition, there are 5 alternatives provided, namely Mandiri bank, BCA bank, BRI bank, BNI bank, and BTN bank. Based on the results of calculations using the Entropy method, the first order of criteria prioritized by customers in choosing a bank based on the weight of the criteria is the bank and ATM accessibility criteria (K7) which has the highest weight of 0.307. Then, using the combined Entropy and PROMETHEE II method shows that bank BCA (A3) ranks first with the highest net flow value of 0.977. Keywords: Entropy, PROMETHEE II, Bank